The potential of copper-resistant bacteria Acinetobacter sp. strain CN5 in decolorizing dyes - WAHYU IRAWATI; REINHARD PINONTOAN; BELLEN MOURETTA; TRIWIBOWO YUWONO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Irawati W, Pinontoan R, Mouretta B, Yuwono T. 2021. The potential of copper-resistant bacteria Acinetobacter sp. strain CN5 in decolorizing dyes. Biodiversitas 23: 680-686. Bacteria with multi-resistance to copper and dyes may be employed in bioremediation of copper and dye waste more effectively than physical or chemical remediation. This study aims at determining the effect of the addition of various textile dyes and copper on the growth of Acinetobacter sp. CN5 and its ability to decolorize dyes. The dye resistance test was carried out by inoculating bacterial isolates into Luria Bertani media containing 50, 100, 150, 200, 250, 300, 350, 400, 450, and 500 ppm dyes. The twelve dyes used in the test were methylene blue, malachite green, congo red, mordant orange, reactive black, direct yellow, basic fuchsine, reactive orange, dispersion orange, remazol red, wantex yellow, and wantex red. The decolorization activity was analyzed by spectrophotometry at a 300-900 nm wavelength. The study results demonstrated that bacteria thrived in media containing 50 ppm of all dyes, except malachite green dye. Acinetobacter sp. CN5 was found to be resistant to up to 500 ppm methylene blue, basic fuchsine, and wantex red and resistant to congo red at 450 ppm. Acinetobacter sp. CN5 was also able to decolorize methylene blue, congo red, basic fuchsine, and red wantex by 57.64%, 53.17%, 91.37%, and 67.50%, respectively. The addition of 5 mM CuSO4 to the medium increased the ability of Acinetobacter sp. CN5 to decolorize the congo red from 57.64% to 82.58%.